Смерть і поховальні звичаї та обряди турків - Рухі Ерсой (Народна творчість та етнографія, 2010)
The phenomenon of death occupies very large place in Turkish culture. In daily life it is an important issue, both in the pre-Islamic period and Islamic modern times. This article investigates religious and cultural aspects of death in Turkey: superstitions, signifying and portending death, rites and rituals performing at the time of death, preparation of the dead for its disposal, its burying, and beliefs, rites and rituals related to post-burial customs. Ölüm olgusu Türk kültüründe geniş bir yer işgal eder. Hem ‹slam öncesi hem de günümüzde, günlük hayatta ölüm, çok önemli bir konudur. Bu makalede, ölümün Türkiye’deki dini ve kültürel yönü incelenecektir. Bu konular şunlardır: ölümü haber veren ve ölümü engelleyen inanç ve uygulamalar, ölüm anında gözlemlenen inanç ve uygulamalar, ölünün defne hazırlanması, defin sonrası inanç ve uygulamalar.